Chili peppers in natura and freeze-dried: physicochemical, proximate, microbiological and bioactive compounds characterization - Lemos, Lúcia Mara dos Reis; Silva, Maria Claudevânia Rabelo da; Aquino, Clarissa Maia de; Almeida, Érica Jamily do Nascimento; Santos, Sandra Maria Lopes dos; Monte, Antonia Lucivânia de Sousa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Chilli pepper (Capsicum frutescens L.) is highlighted for its content of macronutrients and bioactive compounds, such as vitamins and phenolic compounds with antioxidant potential, being used as a spice in Brazilian cuisine. This work aims to analyze the physicochemical, proximate, mineral and microbiological composition, in addition to quantifying bioactive compounds and the antioxidant capacity of chilli pepper in natura and lyophilized form. Fresh and freeze-dried peppers were evaluated in terms of their physicochemical characteristics (pH, water activity, titratable acidity and total soluble solids), centesimal (protein, lipids, moisture, ash, reducing and non-reducing carbohydrates and caloric value) mineral (macro and microminerals) and microbiological (total coliforms, thermotolerants, molds and yeasts and Salmonella research). It was observed that the chilli peppers in natura and freeze-dried showed good nutritional composition, rich in bioactive compounds with antioxidant potential. Drying by lyophilization did not affect the components evaluated.